Genome-wide identification and characterization of lipoxygenases gene family in Luffa aegyptiaca revealed downregulation of LOX genes under heat stress - Huang Hao; Zhuzheng Xue; Yongping Li; Huifei Ma; Qingfang Wen; Lianyu Lin; Haisheng Zhu (Scientific Reports)
Abstract Lipoxygenases (LOXs) are key enzymes in plant lipid metabolism and stress responses, yet their genomic organization and functional dynamics in Luffa aegyptiaca—a species of culinary, medicinal, and ornamental importance—remain unexplored. Here, we present the first genome-wide identification and characterization of the LOX gene family in L. aegyptiaca, revealing 29 LOX genes, including 14 members of 13S-lipoxygenases (13-LOX) and 15 members of 9S-lipoxygenases (9-LOX), respectively. Notably, tandem duplication events shaped the expansion of LOX genes, with 24 genes clustered in two loci, suggesting functional diversification to enhance environmental adaptability. Phylogenetic analysis demonstrated evolutionary conservation of LOX genes across Cucurbitaceae species, while collinearity analysis highlighted conserved genomic organization. Promoter cis-element profiling identified stress- and hormone-responsive motifs, implicating LOX genes in developmental and stress regulatory networks. Tissue-specific expression patterns revealed 18 LOX genes predominantly expressed in tendril, fruit, root, and male flower, linking them to organ-specific physiological roles. Crucially, under heat stress, 9 out of 11 expressed LOX genes were significantly downregulated, indicating their potential role in thermal stress adaptation through metabolic reconfiguration. This study provides foundational insights into the LOX family’s contribution to L. aegyptiaca’s resilience and offers genetic targets for breeding strategies to improve stress tolerance in cucurbit crops.